SOCIO-CULTURAL PECULARITIES OF ARTIFICIAL LANGUAGES UNDER THE CONDITION OF INFORMATION - Антіпова, О. П. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The socio-cultural features of artificial languages are analyzed in the article through the prism of information process as one of the dominant in modern society.